La prueba para mejor resolución frente al principio de impulso procesal y la disposición del Art. 160 del COGEP, en Guaranda año 2023. - Canchig Asimbaya Brandon Bruce (2025)
This research analyzes the tension between the application of evidence for better resolution and the fundamental principles of Ecuadorian civil procedure, specifically the principle of procedural impulse and judicial impartiality enshrined in Article 160 of the Organic General Code of Procedures test to better solve, authorized by Article 168 of the COGEP, allows the judge to request additional evidence to clarify the facts, even if it has not been proposed by the parties. While this tool seeks a just decision in the face of insufficient evidence, its application can affect the procedural balance and the right to defense. The principle of procedural impulse, on the other hand, establishes that the parties are responsible for providing the necessary evidence, while Article 160 of the COGEP emphasizes the judge's impartiality. This research poses the question: How can the application of evidence for better resolution, within the framework of the principle of procedural impulse and Article 160 of the COGEP, affect the procedural balance and the right to defense in Ecuadorian civil proceedings? Through the analysis of doctrine, jurisprudence, and the COGEP, this research seeks to determine whether the application of the evidence for better resolution, as it currently stands, creates procedural imbalances and affects the right to defense. Finally, recommendations are proposed for a more coherent and rights-guaranteeing application of this tool, seeking a more just, efficient, and respectful procedural system that upholds fundamental rights. The construction of the theoretical framework of this study was based on information obtained through a questionnaire, used as a tool to collect data that supports the key concepts of the research. Keywords: evidence for better resolution, principle of procedural impulse.